Low energy electron microscopy study of tiered 'wedding-cake' island formation of bi-layer graphene by using chemical vapor deposition technique - Syed Mohd Jaafar, Syed Muhammad Hafiz; Ahmad Kamal, Shafarina Azlinda; Busayaporn, Wutthikrai; Lim, Hong Ngee (2018)
Mono-layer graphene shows zero-bandgap dispersion relation which differ from bi- and multi-layer graphene that open up its energy bandgap. Therefore, bi- and multi-layer grapheneare preferable in electronics and photonics applications. It is known that chemical vapor deposition (CVD) technique produces high-quality graphene, however the major challenge will be to fabricate a large area bi-layer graphene. Herein, we report a study of the mechanism of uniform tiered ‘wedding-cake’ graphene island growth by using copper oxide nanoparticle as a nucleation seed. The stacking order of the multi-layer graphene island is clearly depicted through Low Energy Electron Microscopy (LEEM). The growth can be controlled by changing the hydrogen flow rate which affects the etching of graphene edges. By implying the vapor trapping mechanism, the seeding can be done simultaneously with the bi-layer graphene growth by using a novel single-step CVD fabrication process.